2009
DOI: 10.1002/art.24847
|View full text |Cite
|
Sign up to set email alerts
|

Continuous occurrence of both insufficient neovascularization and elevated vascular permeability in rabbit proximal femur during inadequate repair of steroid‐associated osteonecrotic lesions

Abstract: Objective. To examine the features of the intraosseous vasculature, the size of the marrow stem cell pool (MSCP), and expression of vascular endothelial growth factor A (VEGF) during inadequate repair of steroid-associated osteonecrotic lesions in rabbits.Methods. Steroid-associated osteonecrosis was induced in male rabbits. At 0, 1, 2, 4, and 6 weeks postinduction, vascularization and permeability indices were quantified by dynamic magnetic resonance imaging (MRI). In addition, the size of the MSCP in the hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 45 publications
1
65
0
Order By: Relevance
“…Osteogenesis and neovascularization play important roles during bone repair. In addition to the impaired activity of MSCs in the steroid-associated osteonecrosis rabbit model, it has been reported that there are effects on hematopoietic stem cells in this model [40]. Neovascularization is thought to be the result of hematopoietic stem cells and endothelial progenitor cell activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Osteogenesis and neovascularization play important roles during bone repair. In addition to the impaired activity of MSCs in the steroid-associated osteonecrosis rabbit model, it has been reported that there are effects on hematopoietic stem cells in this model [40]. Neovascularization is thought to be the result of hematopoietic stem cells and endothelial progenitor cell activity.…”
Section: Discussionmentioning
confidence: 93%
“…This might be because there were more, and smaller, new vessels in LIPUS-treated limbs. Because sufficient blood flow is a fundamental prerequisite for bone repair [40], LIPUS may be a potential approach for improving treatment of early-stage steroid-associated osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A histogram was generated to display the thickness of the angiographic vessels. (30,34) Histological evaluation After decalcification by 10% EDTA, the proximal femurs were embedded in paraffin and cut into 5-mm-thick sections along the coronal plane, except for those used for fluorescence labeling. Sections were stained with H&E for routine histology and with tartrate-resistant acid phosphatase (TRAP; Sigma Diagnostics, St. Louis, MO, USA) for identification of osteoclasts.…”
Section: Microangiographymentioning
confidence: 99%
“…(43) Appositional bone formation with osteoblast-like cells around the osteonecrotic lesion was classified as reparative osteogenesis, whereas fibrotic tissue creep linked to necrotic bone resorption was classified as destructive repair. (30) Evaluation of the repair pattern was done as follows: the entire area of each section, including epiphysis and metaphysis, was examined based on the characteristic histopathological features blindly by two pathologists. We quantified the destructive repair region and the reparative osteogenesis region on the entire section of each specimen.…”
Section: Microangiographymentioning
confidence: 99%
See 1 more Smart Citation